Navigating Aging in a Hypermodern Society: A Qualitative Study on Social Integration and Psychological Resilience among Elderly Taiwanese in Urban Taipei - Meng-chian, Ho (International Journal of Science and Society, 2025)
Urbanization and technological advancement in hypermodern societies create unique social and psychological challenges for aging populations. In Taiwan, one of Asia’s most rapidly modernizing countries, older adults in urban centers encounter increasing risks of social isolation and psychological stress. This literature review examines how elderly individuals in Taipei maintain social integration and psychological resilience amid shifting family structures and digital disruption. The study draws on interdisciplinary research in gerontology, sociology, and urban studies, synthesizing peer-reviewed sources published between 2010 and 2024. Findings reveal that many elderly Taiwanese experience disconnection from traditional family systems and struggle with digital adaptation, yet they rely on cultural norms, spiritual practices, and community-based programs to maintain well-being. The review also highlights a research gap concerning the impact of digital exclusion on mental health. This paper argues that aging policies in modern societies must address socio-cultural identity, psychological support systems, and technological inclusion to enhance the quality of life for older adults.